Short communication: β-Lactam resistance and vancomycin heteroresistance in Staphylococcus spp. isolated from bovine subclinical mastitis - Mello, Priscila Luiza [UNESP]; Pinheiro, Luiza [UNESP]; Martins, Lisiane de Almeida; Brito, Maria Aparecida Vasconcelos Paiva; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (American Dairy Science Association, 2017)
The use of antimicrobial agents has led to the emergence of resistant bacterial strains over a relatively short period. Furthermore, Staphylococcus spp. can produce β-lactamase, which explains the survival of these strains in a focus of infection despite the use of a β-lactam antibiotic. The aim of this study was to evaluate the resistance of Staphylococcus spp. isolated from bovine subclinical mastitis to oxacillin and vancomycin (by minimum inhibitory concentration) and to detect vancomycin heteroresistance by a screening method. We also evaluated β-lactamase production and resistance due to hyperproduction of this enzyme and investigated the mecA and mecC genes and performed staphylococcal cassette chromosome mec typing. For this purpose, 181 Staphylococcus spp. isolated from mastitis subclinical bovine were analyzed. Using the phenotypic method, 33 (18.2%) of Staphylococcus spp. were resistant to oxacillin. In contrast, all isolates were susceptible to vancomycin, and heteroresistance was detected by the screening method in 13 isolates. Production of β-lactamase was observed in 174 (96%) of the Staphylococcus spp. isolates. The mecA gene was detected in 8 isolates, all of them belonging to the species Staphylococcus epidermidis, and staphylococcal cassette chromosome mec typing revealed the presence of type I and type IV isolates.
Keywords: cattle; mecC and mecA; resistance; staphylococci; β-lactam